Death by meeting a leadership fable-- about solving the most painful problem in business - Lencioni, Patrick 1965- (Jossey-Bass, 2004)
Casey McDaniel had never been so nervous in his life. In just ten minutes, The Meeting, as it would forever be known, would begin. Casey had every reason to believe that his performance over the next two hours would determine the fate of his career, his financial future, and the company he had built from scratch. "How could my life have unraveled so quickly?" he wondered. In his latest page-turning work of business fiction, best-selling author Patrick Lencioni provides readers with another powerful and thought-provoking book, this one centered around a cure for the most painful yet underesti
Print version record
Keywords: Business meetings; Réunions d'affaires; BUSINESS & ECONOMICS; Business Communication; Meetings & Presentations